2020
DOI: 10.1111/bjd.19601
|View full text |Cite
|
Sign up to set email alerts
|

Patient age and risk of recurrence of primary melanoma at high risk of spread

Abstract: underlying haematological condition. To our knowledge, this is the first report describing efficacy of ICI for NMSC in this context. The successful experiences with ICI in our cases provide important insights relevant to the clinical management of such patients. Firstly, our cases add to the scant literature supporting that patients with NMSC who may be relatively immunocompromised due to concurrent haematological malignancies can still respond to ICI. 7 Secondly, our experiences suggest that JAK inhibition wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…A systematic review 8 has shown that most MUP diagnoses occur in the 50 to 69 year age group and that males are twice as likely as females to be diagnosed with MUP, features confirmed in the present study, apart from the Italian cohort (again, likely due to small numbers, although other explanations such as different cultural norms are also possible). These findings are consistent with the epidemiological features of thick (advanced) primary cutaneous melanoma, 14,15 the male predominance attributed to the greater delay among men in seeking attention for suspicious skin lesions. 1 Moreover, as melanoma detection has improved steadily over the last few decades, as evidenced by increasing incidence of thin primaries, 16 the relative incidence of MUPs has also decreased, from 5.1% in studies before 1980, to 2.7% in those conducted after 1980.…”
Section: Discussionsupporting
confidence: 86%
“…A systematic review 8 has shown that most MUP diagnoses occur in the 50 to 69 year age group and that males are twice as likely as females to be diagnosed with MUP, features confirmed in the present study, apart from the Italian cohort (again, likely due to small numbers, although other explanations such as different cultural norms are also possible). These findings are consistent with the epidemiological features of thick (advanced) primary cutaneous melanoma, 14,15 the male predominance attributed to the greater delay among men in seeking attention for suspicious skin lesions. 1 Moreover, as melanoma detection has improved steadily over the last few decades, as evidenced by increasing incidence of thin primaries, 16 the relative incidence of MUPs has also decreased, from 5.1% in studies before 1980, to 2.7% in those conducted after 1980.…”
Section: Discussionsupporting
confidence: 86%
“…The Norwegian Malignant Melanoma Registry (NMMR) was established under the CRN in 2008, and information on tumour thickness for incident cases since 2008 was obtained from the NMMR. For melanoma cases diagnosed before 2008, information on tumour thickness was extracted manually by the CRN’s experienced melanoma registrars from histopathological reports in the CRN archive 24 .…”
Section: Methodsmentioning
confidence: 99%
“…9 However, despite these trends, melanoma mortality continues to rise in many countries 10 due to older adults presenting with thick rapidly growing primary melanomas of nodular subtype. 11,12 In the absence of prospective studies of diet with melanoma mortality as outcome, measured tumour thickness at diagnosis can serve as a surrogate for risk of mortality. Evidence of discretionary dietary factors that might modify the rapid growth of thick melanomas would be an important addition to clinical knowledge for public health benefit.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for the dearth of such studies is the generally high survival of today's melanoma patients who tend to be diagnosed with thin tumours with excellent prognosis 9 . However, despite these trends, melanoma mortality continues to rise in many countries 10 due to older adults presenting with thick rapidly growing primary melanomas of nodular subtype 11,12 . In the absence of prospective studies of diet with melanoma mortality as outcome, measured tumour thickness at diagnosis can serve as a surrogate for risk of mortality.…”
Section: Introductionmentioning
confidence: 99%